Strategi Perlakuan Akuntansi dalam Biaya Pemeliharaan dan Perolehan Aset : (Study Kasus Implementasi PSAK 16 dalam Memaksimalkan Nilai Aset pada PT AI) - Roberto Josua F Hasibuan; Rimi Gusliana Mais (AKUNTANSI 45, 2024)
This research aims to examine the application of PSAK 16 of Fixed Assets and the accounting treatment in recording asset maintenance and repair costs to maximize the value of company assets. The research methodology involves quantitative and qualitative analysis of historical data on maintenance, asset acquisition, and asset valuation from the PT.AI. The research results show that the implementation of Fixed Asset recording in companies follows the standards of PSAK 16. Fixed asset maintenance and repair costs are divided into two cost groups, namely revenue expenditure and capital expenditure. Management policy wants to recognize assets above the acquisition value of 5 million. The recommendation for companies is that material costs that have benefits for more than 1 year should be included in capital expenditure. Apart from that, this research also highlights the importance of technology integration in the maintenance process for cost efficiency and optimal increase in asset value.